Co-simulation of continuous and categorical variables: application in the Shuiyindong gold deposit modeling - Zeng, Jianpeng; Hong, Yurong; Wang, Chengbin; Chen, Jianguo; Liu, Jianzhong (Frontiers in Earth Science, 2026)
IntroductionAccurate characterization of concealed orebodies in complex geological environments remains a principal challenge in deep mineral exploration. In particular, the strong spatial interdependence between continuous (e.g., grade) and categorical (e.g., lithology) variables greatly increases the complexity of three-dimensional modeling and uncertainty assessment.MethodsIn this study, we implement a unified co-simulation workflow integrating Plurigaussian simulation and the Turning Bands algorithm to co-simulate ore grade and rock type data from drillholes. The approach explicitly captures both auto-correlations and cross-correlations between variables, enabling realistic spatial reproduction of orebody geometry and internal heterogeneity. ResultsThe resulting three-dimensional stochastic models effectively represent the spatial anisotropy and variability of mineralization, accurately delineating orebody continuity and its lithological controls.DiscussionThese results not only enhance the understanding of ore distribution at the Shuiyindong deposit but also identify zones with high spatial variability that warrant further deep exploration. Although sparse drilling data introduce local uncertainty, the workflow demonstrates a practical framework for three-dimensional geological modeling and uncertainty management in similarly heterogeneous ore deposits.